Cloning and spatio-temporal expression analysis of the CRABS CLAW gene involved in extrafloral petiolar nectary development in Passiflora alata Curtis and Passiflora cincinnata Masters - Sodrzeieski, Pedro Alexandre (2022)
The genus Passiflora includes more than 500 species distributed in five subgenera, of which the subgenus Passiflora is the most representative. Passiflora alata and P. cincinnata are species belonging to this subgenus and are of economic and nutraceutical importance. Extrafloral nectaries are a striking feature in this botanical group, being responsible for several important processes in attracting natural enemies of predators of these species. In addition, extrafloral nectaries are also defense structures, mimicking predator eggs to avoid oviposition and possessing several compounds to reduce herbivory. The genetic mechanisms of nectary formation are still poorly understood; however, it is known that there are two genes that act as master regulators of this process: CRABS CLAW (CRC) and STYLISH (STY). STY is responsible for the formation of nectaries in basal eudicots, while CRC, in nuclear eudicots. In Arabidopsis floral nectaries, stimulated by ARABIDOPSIS RESPONSIVE FACTORS 6/8, CRC, belonging to the YABBY family of transcription factors, initiates its expression at the site where the nectary will be formed, and is limited to its interior. The spatial regulation of CRC expression is controlled by genes such as LEAFY (LFY) and APETALLA1 (AP1) that will inhibit its expression outside the nectary tissues. Since Passifloras are species belonging to the nuclear eudicots and a CRC fragment was found in a transcriptome of leaf primordium in P. cincinnata, the aim of this work was to investigate morphological and anatomical aspects of petiolar nectary development and CRABS CLAW gene expression at three distinct developmental stages in Passiflora alata and Passiflora cincinnata. For this, petiolar nectaries were collected from both species using three different stages of leaf development as a guide: primordium, expanding and expanded. Analyses of morphology under stereomicroscope, photomicroscope and scanning electron microscope, besides in situ hybridization and quantitative real-time PCR (RT-qPCR) were performed. The petiolar nectaries of P. cincinnata have an oval shape while those of P. alata are calyx-shaped. The nectaries of both species have similar anatomical aspects presenting a division into three distinct tissues: epidermis and nectariferous and subnectariferous parenchyma. The epidermis is multiseriate only in the crater region, the nectariferous tissue is composed of smaller cells with dense cytoplasm and those of the subnectariferous by larger, less dense cells and the presence of vascular tissues. CRC expression was restricted to the interior of the nectaries and its expression level peaked at the expanding leaf stage, showing similar values between the primordium, and expanded leaf. Due to the inefficiency of the primers used, it was not possible to obtain the complete expressed sequence by means of RACE. There is strong evidence that CRC acts as a key regulator in petiolar nectary formation in P. cincinnata and P. alata. Keywords: CRABS CLAW. Gene expression. Nectary Morphoanatomy. Passifloraceae. Secretory structures.